Nutrition composition and anthocyanin content of mulberry fruits (Morus alba L.) by different ripening stage grown in the south of Thailand, applicants in sorbet and sherbet ice-cream and analysis of physical, chemical and sensory evaluation - Sangteerakij, Duangkamon; Rodyu, Sauwanee; Junden, Sirisopa (Emirates Journal of Food and Agriculture, 2022)
This experiment was study on properties of each ripening stage of mulberry fruits and conducted study of physical and chemical properties of mulberry fruit at each ripening stage and apply mulberry fruit in ice cream products. Mulberry at fully-ripened stage showed higher phenolic, flavonoid and anthocyanin content. Mulberry fruits were used to make four different types of ice cream; sorbet, sherbet, milk, and yogurt. The sensory qualities of mulberry ice cream were studied (9-point hedonic scale), and the results revealed that mulberry sherbet ice cream had the highest overall acceptability, followed by mulberry sorbet ice cream. The physical, chemical, nutrition composition, and microbiological properties of mulberry sherbet and sorbet ice cream were investigated further. Due to the presence of fresh milk in the composition, sherbet ice cream has a higher overrun and lightness (L*) than sorbet ice cream. The mulberry sherbet ice cream had more incredible energy, energy from fat, total fat, saturated fat, cholesterol, protein, total carbohydrates, calcium, dietary fiber and phenolic compounds. This study shows that mulberry has beneficial properties in terms of consumer acceptance and health benefits, particularly in mulberry sherbet ice cream. All mulberry ice creams had been sanitized and were suitable to consume. As a result, mulberry ice cream formulations can add value to agricultural products and suggested for commercialization.